Peranan Program Keagamaan Terhadap Pemulihan Konsep Kendiri Banduan Wanita di Malaysia: The Role of Religious Program to Recovery Self Concept of Women Offenders in Malaysia - Abdul Jalil, Siti Jamiaah; Md Yusoff, Yusmini; Ismail, Rozmi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
According to the statistics of Malaysian Prisons Department (MPD), women offender population is increasing from year to year (in 2011; 8,230 people, in 2012; 8,774 people, in 2013; 11,221 people). Some studies showed, the tendency to take action deviating is associated with an individual self-concept. In the meantime, the MPD has developed a recovery module to prisoners. Among the major modules implemented are modules religious. Consequently, the study was conducted to identify the current state of the self-concept of women offenders and identify the role of religious programs on the recovery of their self-concept. Basic Scale Questionnaire Religious Values ​​Devian (BRVSD) was used to determine the extent of respondents religiosity and Six Factor Self Concept Scale (SFSCS) was used to determine the state of their self-concept. A total of 141 women offenders involved in the study. The results showed a recovery program through religious approach be able to influence self-concept of women offenders. Accordingly, high religious understandingand strength of faith as well as great implementation of worship and shari`ah can develop more positive self-concept of women offenders.